PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI GOOGLE SLIDES MATERI SISTEM PENCERNAAN MAKANAN PADA MANUSIA BAGI SISWA KELAS VIII SMP - Binsasi, Fransiskus Xaverius Deddy Baki; Sila, Vinsensia Ulia Rita; Shidik, Muhammad Amran (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
In this study, the aim was to produce learning media based on the Google Slides application for natural science subjects on the human digestive system at Fatumfaun Public Middle School and then to find out the feasibility of Google Slides-based learning media for natural science subjects on the food digestive system for humans at public junior high schools. Fatumfaun based on the results of expert reviews and trials. Research and development (Research and Development) is a method used in this investigation. Both qualitative and quantitative data kinds are employed. The results of the assessment of media experts have an average value of 92.30% and are stated to be very good for testing. The results show that the material expert's assessment obtained an average value of 96.67% and was stated to be very good for testing. Based on Table 5, the trial of learning media products based on the Google Slides application is included in the very good category to be tested at Fatumfaun Public Middle School with an average score of 89.25% of student assessment results. The development of Google Slides application-based learning media for the digestive system material in humans that was developed was declared feasible to be tested.